Noun-verb and pronoun-verb concatenation : a linguistic examination of peculiarities - Nurul Asilah binti Mohd Khaidir (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2018)
This study aims at examining peculiarities in noun-verb and pronoun-verb conjugations. It also seeks to find whether there are explanations for these peculiarities that occur in the said conjugations. This study is carried out by employing textual analysis and using the analytical framework adapted from Contini-Morava and Goldberg's (1995) model based on the sign oriented approach to examine the noun-verb and pronoun-verb conjugations in the prescribed texts (e.gexpository texts). The findings show that peculiarities or ambiguities do occur in the conjugations of noun-verb and pronoun-verb with the presence of the inflection –ed (past tense/time) to the verbs, modals (e.g will, can, could, should, etc) paired with verbs, to+verbs in the base form (infinitives) and verbs inflected with –ing. These grammatical features seem ambiguous because they do not conjugate with one another in terms of the noun number and the verb number agreement. It is found that these ambiguities are used by writers/speakers as indicators to readers/listeners to showthe focus of the message being conveyed instead of looking at the noun number and verb number agreement in the sentence(s). This means that the main emphasis is not on noun-verb number agreement. It is also found that the usage of ambiguities is one of the ways writers choose to express contextual number-specification which are not in-line with the SVA rule which allow writers/speakers to alter the application of number agreement of nouns and verbs to the singular and plural contexts in objective terms and yet still be phonologically, morphologically and grammatically correct.